2017
DOI: 10.1111/maec.12433
|View full text |Cite
|
Sign up to set email alerts
|

Oceanographic influences on the distribution and relative abundance of market squid paralarvae (Doryteuthis opalescens) off the Southern and Central California coast

Abstract: Market squid (Doryteuthis opalescens) are ecologically and economically important to the California Current Ecosystem, but populations undergo dramatic fluctuations that greatly affect food web dynamics and fishing communities. These population fluctuations are broadly attributed to 5–7‐years trends that can affect the oceanography across 1,000 km areas; however, monthly patterns over kilometer scales remain elusive. To investigate the population dynamics of market squid, we analysed the density and distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…From our results, we hypothesize patch use may be synced with the timing of nocturnal prey movements, assuming foraging is the goal of their ARS movements. Some nocturnal invertebrates exhibit varying degrees of diurnal vertical migrations (DVMs) [81,82], and others (e.g., urchins) may take time to emerge from their protective daytime shelter habitats after sunset [83,84]. Therefore, horn sharks may time their movements to locate a patch approximately 3 h after sunset as it optimizes their chances of more easily locating dense prey patches.…”
Section: Discussionmentioning
confidence: 99%
“…From our results, we hypothesize patch use may be synced with the timing of nocturnal prey movements, assuming foraging is the goal of their ARS movements. Some nocturnal invertebrates exhibit varying degrees of diurnal vertical migrations (DVMs) [81,82], and others (e.g., urchins) may take time to emerge from their protective daytime shelter habitats after sunset [83,84]. Therefore, horn sharks may time their movements to locate a patch approximately 3 h after sunset as it optimizes their chances of more easily locating dense prey patches.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that D. opalescens paralarvae migrate to the surface in the first 6 h after hatching ( Sidie and Holloway, 1999 ) and perform vertical diel migrations from 30 m (day) to the surface (night) by 14 days ( Zeidberg and Hamner, 2002 ). The highest abundances of paralarvae are found in the neuston layer at night associated with cooler SST (13–16.5°C; Koslow and Allen, 2011 ; Van Noord and Dorval, 2017 ). Our experimental results are consistent with field studies and attest that paralarvae can actively influence their fine-scale distribution by migrating vertically, becoming aggregated in areas of high food availability and adjust their dispersal patterns in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Squid paralarvae are negatively buoyant ( Sidie and Holloway, 1999 ; Martins et al, 2014 ), as a result, paralarvae sink when swimming stops and must constantly jet to stay suspended and this is energetically costly. Forming schools early in life in areas of gradients of flow (vertical turbulent mixing) could assist paralarvae in holding position, minimizing the energy allocated to jetting and aggregate them with their food in upwelling areas ( Zuev, 1964 ; Koslow and Allen, 2011 ; Van Noord and Dorval, 2017 ). Indeed, D. opalescens paralarvae have been found aggregated within cyclonic gyres and eddy-induced upwelling in the Southern California Bight, where vertical mixing occurs at the frontal zone of warm and cold waters ( Zeidberg and Hamner, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, peak synchronous spawning was temporally dynamic, in that the month of peak paralarval hatching shifted from January, during 2013-2014, to December, the following hatching season. This temporal shift is likely explained by gradually warming ocean temperatures in the CCE, which causes squids, including the California market squid, to mature faster, spawn, and hatch earlier in the season (Forsythe, 2004;Van Noord & Dorval, 2017). Jackson and Domeier (2003) of California led Dosidicus gigas to adopt a small size-at-maturity phenotype, leading to the collapse of that fishery (Frawley et al, 2019).…”
Section: Synchronous and Protracted Spawningmentioning
confidence: 99%